2012
DOI: 10.1017/s1355617711001767
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth and Neuropsychological Performance in Very Low Birth Weight Preschoolers

Abstract: In this study we examined the association between intrauterine growth, indexed either as a categorical variable or continuous dimension, and neuropsychological outcome, in a very low birth weight (VLBW) sample of 143 preschoolers. When the commonly used split at the 10th percentile rank was applied to classify intrauterine growth restriction (IUGR), we found that the growth restricted group (n = 25) exhibited significantly poorer performance in the global motor domain, but not on any other neuropsychological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Risk factors for lower scores on the visual-motor coordination component were lower gestational age, VSGA status, and BPD. Associations between gestational age, 7 fetal growth, 24 and BPD 25 and visual-motor integration have been shown in previous research.…”
Section: Discussionsupporting
confidence: 65%
“…Risk factors for lower scores on the visual-motor coordination component were lower gestational age, VSGA status, and BPD. Associations between gestational age, 7 fetal growth, 24 and BPD 25 and visual-motor integration have been shown in previous research.…”
Section: Discussionsupporting
confidence: 65%
“…Intra‐uterine growth restriction has long been identified as a risk factor for a wide variety of developmental problems in term and preterm children . In particular, children born very preterm with intra‐uterine growth restriction are at increased risk, not only for motor problems but also for behavioural and cognitive impairments . Recently, it has been reported that the prevalence of fine motor impairments (using the MABC <P15 as a cut‐off point) is increased in very preterm children with growth restriction compared with non‐growth‐restricted preterm children (68% vs 43%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional deficiency and growth failure in infancy and early childhood have repeatedly been found to be associated with neuroanatomical abnormalities and cognitive deficits. 2729 …”
Section: Discussionmentioning
confidence: 99%